Energy Auditing as a Tool for Outlining Major Inefficiencies: Results from a Real Water Supply System. (2015) - Mamade, Aisha; Sousa, Catarina; Marques, Ana; Loureiro, Dália; Alegre, Helena; Covas, Dídia
Abstract: The application of a novel energy auditing scheme in a real water supply system and its sub-systems to determine major sources of energy inefficiency is presented. This scheme has been consolidated in the Portuguese National Initiative for the management of water-energy losses (www.iperdas.org ). Within this initiative, 17 water utilities have carried out energy audits following a two-step procedure: (i) simplified energy auditing and calculation of efficiency metrics for the global system and for sub-systems and (ii) detailed energy auditing for critical sub-systems. The case-study of Águas do Sado water utility is presented to illustrate the application of this approach. This system has 25% of non-revenue waterand consumes 5.5 GWh per year, which is approximately twice the minimum energy required. The analysis of therespective 17 sub-systems has shown that the major inefficiencies are due to topography constraints, to water losses and to the lack of intermediate service pressure levels.